Optimization of pH to Bacteriocin Production by Lactobacillus Acidophillus Against Methicillin-Resistant Staphylococcus Aureus - Rivaldi, Fajar; Suryani, Lilis (Universitas Muhammadiyah Yogyakarta, 2025)
Introduction: Methicillin-Resistant Staphylococcus aureus (MRSA) is a strain of Staphylococcus aureus that has developed resistance to the antibiotic’s methicillin and beta lactams. MRSA has infected approximately 11 million people, and causes skin and soft tissue infections, bacteremia, pneumonia, osteomyelitis, endocarditis, meningitis, and sepsis. MRSA can be transmitted through hands, contact between patients and other people, nurses or doctors who do not wash their hands, and even health workers who have MRSA colonies on their hands and front of the nose without symptoms. Purpose: This study aims to determine the effect of pH on the activity of bacteriocins produced by Lactobacillus Acidophilus against MRSA. Methods: This research uses quasi-experimental laboratory methods. Lactobacillus acidophilus was grown in liquid MRS media for 48 hours. Bacteriocin was obtained by centrifuging liquid MRS containing bacteria at a speed of 6000 rpm for 40 minutes. The liquid formed was tested for its antibacterial effect against MRSA bacteria using the Kirby Bauer method. Bacteriocins were treated with various different pHs, that is; 2, 4, 6, 8, 10. The diameter of the inhibition zone formed during the testing process is measured in millimeters. Data were analyzed using the ANOVA method. Finding: The bacteriocin activity produced by Lactobacillus acidophilus against MRSA showed an average diameter of the inhibition zone of 2.90 mm. The broadest spectrum of antibacterial activity was demonstrated in bacteriocins treated with pH 2. Conclusion: This study shows that pH does not affect the antibacterial activity of bacteriocins produced by Lactobacillus acidophilus against MRSA. Originality/Implication: The results of this study prove that various pH treatments do not affect the ability of bacteriocins produced by L. Acidophilus to inhibit/kill MRSA.